Consumer multifaceted trust of central bank digital currency (CBDC) payment in travel and tourism - Chua, Bee-Lia; Amare Ayalew, Zemenu; Kim, Seongseop; Han, Heesup; Ha, Heekyeong (Elsevier, 2025)
This study examined an integrative, multifaceted trust model that links the role of disposition to trust and institution-based trust in producing trusting beliefs and trusting intention. A survey of Korean consumers who are familiar with central bank digital currency (CBDC) and are regularly involved in purchase decision-making about tourism products was conducted to determine the relationships between disposition to trust, institution-based trust, trusting beliefs, and intention to trust CBDC payment. The findings revealed significant links between faith in technology, structural assurance, and situational normality, highlighting the role of personal disposition to trust and institution-based trust in trust formation. Institution-based trust also acted as a mediator between disposition to trust and trusting beliefs in influencing intentions to adopt CBDC payments. By shedding light on the intricate relationship between personal beliefs and situational influences, this study provides guidance on how to cultivate trust and encourage the widespread embrace of CBDC payment in the travel and tourism sectors.